Spontaneous perforation of solitary ulcer of transverse colon - Galanis Ioannis; Dragoumis Dimitrios; Kalogirou Thomas; Lakis Sotiris; Kotakidou Rodi; Atmatzidis Konstantinos (Wolters Kluwer Medknow Publications, 2010)
Spontaneous ruptures of the colon and rectum are extremely uncommon clinical entities and always require laparotomy. A 44-year-old female was admitted with a 12-hour history of severe abdominal pain periumbilically and at the right hypochondrium. The patient was immediately transferred to the department of surgery for close surgical observation. Computed tomography (CT) of the entire abdomen performed just before the operation demonstrated thickening of the wall of the ascending colon with pericolic fat stranding. Surgery revealed a perforation at the antimesenteric wall of the transverse colon and segmental colectomy of the transverse colon was performed. The histological evaluation demonstrated a perforated solitary ulcer of the transverse colon. There are only few known etiologic factors concerning spontaneous ruptures of the colon and rectum and usually none of these causative factors can easily be recognised. Their clinical appearance is most of the times acute abdomen and, despite the use of all appropriate diagnostic methods, the diagnosis is usually set postoperatively.